AI at Elsinore: What Horatio can teach us about Artificial Intelligence - Laqué, Stephan (Journal of Posthumanism, 2024)
This paper argues that the early modern period was already debating questions about the interstices and transitions between humans and machines, much like the ones that govern our engagements with AI today. Looking at Shakespeare’s Hamlet, I will be showing that, next to the ghost, Horatio is another and arguably no less challenging uncanny character on the battlements at Elsinore. While the ghost is situated between the full humanity of a living human being and the inanimate materiality of a dead corpse, Horatio seems to be situated between the full humanity of being “passion’s slave” and the mechanical functioning of a timekeeping and recording device. Horatio, then, is an experiment in artificial intelligence avant la lettre. This paper shows how his reduced, partial, and artificial humanity is explored by the play as it exposes Horatio’s inadequacies.